EFFECTS OF CAPTURE-RELATED INJURY ON POSTCAPTURE MOVEMENT OF WHITE-TAILED DEER - Dechen Quinn, Amy C.; Williams, David M.; Porter, William F.; Fitzgerald, Scott D.; Hynes, Kevin (Journal of wildlife diseases, 2014)
Capture-related injuries or deaths of wildlife study subjects pose concerns to researchers, from considerations for animal welfare to inflated project costs and biased data. Capture myopathy (CM) is an injury that can affect an animal's survival ≤30 days postrelease, but is often difficult to detect without close monitoring and immediate necropsy. We evaluated the influence of capture and handling on postcapture movement in an attempt to characterize movement rates of animals suffering from CM. We captured and global positioning system–collared 95 white-tailed deer (Odocoileus virginianus) in central and northern New York during 2006–2008. Six juveniles died within 30 days postrelease, and necropsy reports indicated that two suffered CM (2%). We compared postcapture movement rates for juveniles that survived >30 days with those that died ≤30 days postcapture. Survivor movement rates (43.74 m/hr, SD = 3.53, n = 28) were significantly higher than rates for deer that died within 30 days (17.70 m/hr, SD = 1.57, n = 6) (P<0.01). Additionally, movement rates of juveniles that died of CM (15.1 m/hr) were 5.1 m/hr lower than those for juveniles that died of other causes ≤30 days postcapture (20.2 m/hr), but we were unable to evaluate this statistically because of insufficient sample size. We found no difference in vital rates (temperature, heart rate, respiration rate) during handling between survivors and juveniles that died within 30 days postcapture but observed that survivors were in better body condition at capture. These results suggest that deer likely to die within the 30-day CM window can be identified soon after capture, provided that intensive movement data are collected. Further, even if necropsy reports are unavailable, these animals should be censored from analysis because their behavior is not representative of movements of surviving animals.